Rekonstruktion des Ursprungs und Neudatierung zweier magischer Gemmen mit Hilfe einer Zauberzeichensequenz - Dzwiza, Kirsten (Zeitschrift für ägyptische Sprache und Altertumskunde, 2020)
There are only a few sequences of ancient magic signs known to us today that have been preserved on multiple artefacts. A previously unnoticed sequence of 17 signs on a gem in the Museum of Fine Arts in Vienna occurs with minor but significant variations on two other gems in the State Museum of Egyptian Art in Munich. The Viennese gem is dated to the 16th century and is documented as a drawing in a 17th century publication. The first Munich gem has been assigned to the Graeco-Roman period. The second gem, which, according to the inventory card of the museum, also belongs to the Graeco-Roman period, is published here for the first time. A comparative study of the three gems and the drawing has lead to a number of new findings, including the re-dating of the Munich gems.